Simulation with Arena - Kelton, W. David; Sadowski, Randall P.; Swets, Nancy B. (New York : McGraw-Hill, 2010)
"Simulation with Arena provides a comprehensive treatment of simulation using industry-standard Arena software. The text starts by having the reader develop simple high-level models, and then progresses to advanced modeling and analysis. Statistical design and analysis of simulation experiments is integrated with the modeling chapters, reflecting the importance of mathematical modeling of these activities. An informal, tutorial writing style is used to aid the beginner in fully understanding the ideas and topics presented. The academic version of Arena and example files are available through the book's website. Verified instructors can also download a 30-seat site license of Arena for use in their course."--Publisher's website.
-- What Is Simulation? -- Fundamental Simulation Concepts -- A Guided Tour Through Arena -- Modeling Basic Operations and Inputs -- Modeling Detailed Operations -- Statistical Analysis of Output from Terminating Simulations -- Intermediate Modeling and Steady-State Statistical Analysis -- Entity Transfer -- A Sampler of Further Modeling Issues and Techniques -- Arena Integration and Customization -- Continuous and Combined Discrete/Continuous Models -- Further Statistical Issues -- Conducting Simulation Studies.
Includes bibliographical references (pages 611-613) and index.
Keywords: Arena (Computer file); Computer simulation